Studi Karakteristik Campuran AC-BC Berdasarkan Limbah Kantong Plastik Sebagai Bahan Tambah - Sri Yuniarti; Rais Rachman; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This research is intended to study the characteristics of a mixture of AC-BC using plastic bag waste as added material. Mixing is done by adding pieces of plastic to the asphalt mixture using a dry method. The method in this research is to conduct a series of testing the characteristics of coarse, fine, and filler aggregates then design the AC-BC mixture composition and Marshall testing to obtain mixture characteristics and Marshall Immersion testing to obtain the residual strength index (IKS). Through the Marshall test, the level of plastic bag waste used is 0%, 0.5%, 1%, 1.5%, and 2%. The results of research conducted at the Road and Asphalt Laboratory of the Faculty of Civil Engineering, Indonesian Christian University, Paulus Makassar, showed that the use of additives in intermediate asphalt concrete mixtures can increase stability values. The stability value due to the addition of plastic to the asphalt mixture increases compared to asphalt mixture without plastic. The level of good addition of plastic to asphalt mix is 2% because in addition to the high stability value, Marshall parameters such as VIM, Flow, VMA, and VFB have also fulfilled the 2018 Directorate General of Highways Specifications.